Radiation of electric, magnetic and toroidal dipoles uniformly moving in an unbounded medium - Afanasiev, G.N.; Stepanovsky, Yu.P. (Вопросы атомной науки и техники, 2001)
We considered the radiation of electric, magnetic and toroidal dipoles uniformly moving in unbounded medium. It turns out that the radiation intensity crucially depends on the mutual orientations of their symmetry axes and the velocity. The behavior of radiation intensities in the neighbourhood of the Cherenkov threshold b = 1/n is investigated. The frequency and velocity regions are defined where radiation intensities are maximal. The comparison with previous attempts is given.